Nischarin Inhibits LIM Kinase To Regulate Cofilin Phosphorylation and Cell Invasion - Ding, Yuemin (American Society for Microbiology (ASM), 2008)
Nischarin is a novel protein that regulates cell migration by inhibiting p21-activated kinase (PAK). LIM kinase (LIMK) is a downstream effector of PAK, and it is known to play an important role in cell invasion. Here we show that nischarin also associates with LIMK to inhibit LIMK activation, cofilin phosphorylation, and LIMK-mediated invasion of breast cancer cells, suggesting that nischarin regulates cell invasion by negative modulation of the LIMK/cofilin pathway. The amino terminus of nischarin binds to the PDZ and kinase domains of LIMK. Although LIMK activation enhances the interaction with nischarin, only phosphorylation of threonine 508 of LIMK is crucial for the interaction. Inhibition of endogenous nischarin expression by RNA interference stimulates breast cancer cell invasion. Also, nischarin small interfering RNA (siRNA) enhances cofilin phosphorylation. In addition, knock-down of nischarin showed branched projection actin structures. Collectively these data indicate that nischarin siRNA may enhance random migration, resulting in stimulation of invasion.